Assessment of Halamphora coffeaeformis Growth and Biochemical Composition for Aquaculture Purposes - Scodelaro Bilbao, Paola G. (2020)
The vast majority of the world’s fishery by-products are utilized in the fish farming industry. However, due to the high cost and unsustainability of these by-products, alternative sources must be found. Marine diatoms produce important amounts of fatty acids, sterols, proteins and carbohydrates. In this work, we assessed the nutritional value of Halamphora coffeaeformis at the exponential growth phase, to determine its suitability for aquafeed. The strain was grown in a photobioreactor at 20 °C for 6 days. The production of proteins, lipids and carbohydrates was determined, and essential fatty acid, sterol and amino acid composition was assessed. The highest values of triacylglycerides (TAG), free and esterified sterols, proteins and carbohydrates were found after 6 days of growth in the photobioreactor. Fatty acid analysis by gas chromatography showed the presence of eicosapentaenoic (EPA) and arachidonic (ARA) in amounts similar to those for fish oils. In terms of sterols, a predominance of stigmasterol was observed, followed by cholesterol. The amino acid composition revealed 50% of them to be among those essential for fish and other aquatic animals. Finally, a suitable amount of carbohydrates was found in H. coffeaeformis cultures. Together, these findings support the use of H. coffeaeformis as an alternative and sustainable source for aquafeed to partially replace the use of fishery by-products.